Estudo do impacto da ampliação de berço e de área de pátio no aumento da capacidade operacional de uma base de apoio offshore - Aguiar, Renato Armani (2013)
In the global competitive landscape ports have always played a prominent role, acting as a driving element for the development of enterprises and regions where they are inserted. In this context also includes the logistics offshore ports who provide support services to maritime units (platforms and rigs), acting as a link in the supply chain logistics of oil and gas. In turn, the port sector in Brazil has undergone a long period without investments in infrastructure begins to show the negative marks that time, with the growth in demand for support services, companies have suffered from the lack of bases port. Therefore, investment in infrastructure is presented as a solution for this late problem and announced that emerges as crucial to avoid a blackout offshore logistics. Thus, this study aims to evaluate the impact of infrastructure expansion in the performance indicators used in a terminal offshore support. Seeking to respond to the proposed objective, was used the simulation tool in order to study the best option for the investor is to invest resources in berths or increasing the patio area. The results show that although the common sense indicate that the increase in operating capacity increases cots, in this case the increase in area for the terminal analysis showed better operating results, and the best option for investment in infrastructure.